The Effectiveness of Using Youtube Video in Improving Students Writing Skill of Procedure Text at the Tenth Grade Of SMA Prima Tembung - Sari, Yeni Darmaika; Asnawi, Asnawi (Education Achievement: Journal of Science and Research, 2024)
The aim of this research was to obtain the empirical evidence about the effectiveness of tutorial video on students’ writing of procedure texts. The method used in this research was a quantitative method and the research design was a quasi-experimental. The sample of this research was at the tenth grade students of SMA Prima Tembung academic year of 2020/2021. They were X IPA-1 class as the experimental class, whereas X IPA-2 class as the control one. Each class consisted of 25 students. The experimental class was taught with tutorial video while the control class was taught with teacher’s presentation or without tutorial video. For sampling technique the researcher used purposive sampling. The instrument used in this research was a written test and the scoring of writing rubric was used to score the students’ writing on the pre and posttest. Based on the calculation, the post-test mean scores of the experimental class was 79.32 while that of the control class was 75.44. Then, the result of statistical hypothesis testing by using independent sample t-test found that on degree of significance 5% (? = 0.05), tobserve was 3.108 while t table was 2.001 or tobserve > t table. Therefore, H0 was rejected and Ha was accepted. Furthermore, the Cohen’s formulation was used in order to know the effect size of tutorial video and the result was 0.80. It proved that tutorial video gave moderate effect and it can be concluded that there was a significant effect of tutorial video on students’ writing of procedure texts at the tenth grade of students SMA Prima Tembung in the academic year of 2020/2021.